Big data maturity model for Malaysian zakat institutions to embark on big data initiatives - Sulaiman H.; Cob Z.C.; Ali N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer software; Information management; Societies and institutions; Software engineering; Computing resource; Informed decision; levels; Management mechanisms; Maturity model; strategy; Structured process; zakat; Big data